2013
DOI: 10.1002/ijc.28186
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in theXRCC1gene modify survival of bladder cancer patients treated with chemotherapy

Abstract: Survival of bladder cancer patients depends on several factors including disease stage and grade at diagnosis, age, health status of the patient and the applied treatment. Several studies investigated the role of DNA repair genetic variants in cancer susceptibility, but only few studies investigated their role in survival and response to chemotherapy for bladder cancer. We genotyped 28 single nucleotide polymorphisms (SNP) in DNA repair genes in 456 bladder cancer patients, reconstructed haplotypes and calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Genetic variation in TP63C/T, TERTC/T, and SLC14A1C/T were also confirmed associated to bladder tumour in European and White population. Multiple SNPs in base excision repair system including XRCC1 modulate the risk of bladder cancer, which modify survival of bladder cancer patients treated with chemotherapy (Sacerdote et al, 2013;Xie et al, 2013). However, individual prediction of disease outcome based on "molecular markers" of bladder cancer is currently not reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation in TP63C/T, TERTC/T, and SLC14A1C/T were also confirmed associated to bladder tumour in European and White population. Multiple SNPs in base excision repair system including XRCC1 modulate the risk of bladder cancer, which modify survival of bladder cancer patients treated with chemotherapy (Sacerdote et al, 2013;Xie et al, 2013). However, individual prediction of disease outcome based on "molecular markers" of bladder cancer is currently not reliable.…”
Section: Discussionmentioning
confidence: 99%
“…La Citt a della Salute e della Scienza, formerly S. Giovanni Battista hospital, in Turin, and were recruited during the years 1994 to 2008 (12,13). In total, 726 patients were recruited, followed up, and included in a survival analysis to investigate the effect on clinical outcome of patients' characteristics.…”
Section: Patientsmentioning
confidence: 99%
“…DNA was extracted from peripheral blood leukocytes as reported by Sacerdote and colleagues (13). The total amount of telomeric DNA was measured by quantitative real-time PCR as previously described by Zee and colleagues (14).…”
Section: Tl Analysismentioning
confidence: 99%
“…Figl et al showed that variants in potential regulatory regions of DNA repair genes might influence disease outcome in melanoma patients and have potentially significant implications for patient surveillance and tailored treatment 63. XRCC1 risk allele may result in resistance to therapy and shorter survival in bladder cancer patients treated with chemotherapy 64. XRCC1 Gln allele genotype showed significant prognostic associations in hepatocellular carcinoma 65.…”
Section: Discussionmentioning
confidence: 99%